Analysis of Bifurcations in a Wind Turbine System Based on DFIG - Saber Khosravi; Mehran Zamanifar; Pouya Derakhshan-Barjoei (Emerging Science Journal, 2018)
This main aim of this study is investigation of the dynamic stability in a grid-connected wing turbine system based on Double Feed Induction Generator (DFIG) using the bifurcation theory. Regarding the overview of stability by Cardenas et. al. [1]. In our research, the proposed system model is simulated based on bifurcation theory in MATLAB software. In each step, one of the controlling or non-controlling parameters is selected. Eigenvalues of system are traced permanently during simulation. According to the change of the eigenvalues of system, due to the change of bifurcation parameter, stability of the equilibrium point and special bifurcations including saddle-node and Hopf bifurcations in the system are determined.